2018
DOI: 10.7567/jjap.57.04fg07
|View full text |Cite
|
Sign up to set email alerts
|

Defect observations of Ni/AlGaN/GaN Schottky contacts on Si substrates using scanning internal photoemission microscopy

Abstract: We have demonstrated the use of scanning internal photoemission microscopy (SIPM) to characterize crystal defects in an AlGaN/GaN heterostructure grown on Si substrates. SIPM enabled the visualization of unusually grown regions owing to cracking of the Si substrates. In these regions, photocurrent was large, which was consistent with leaky current–voltage characteristics. We also found smaller photoyield regions, which may originate from the Al-rich AlGaN regions on hillocks. We confirmed the usefulness of SIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In general, electrical characterization of resistive regions is difficult, but SIPM is able to map them in two dimensions. Figure 22 shows SIPM measurements on AlGaN/GaN high electron mobility transistor (HEMT) wafers on a Si substrate (40). Typically, epitaxial growth of AlGaN/GaN HEMT structures has been performed on sapphire or SiC substrates, which are chemically stable during crystal growth.…”
Section: Two-dimensional Characterization Using Our Scanning Internal...mentioning
confidence: 99%
“…In general, electrical characterization of resistive regions is difficult, but SIPM is able to map them in two dimensions. Figure 22 shows SIPM measurements on AlGaN/GaN high electron mobility transistor (HEMT) wafers on a Si substrate (40). Typically, epitaxial growth of AlGaN/GaN HEMT structures has been performed on sapphire or SiC substrates, which are chemically stable during crystal growth.…”
Section: Two-dimensional Characterization Using Our Scanning Internal...mentioning
confidence: 99%
“…Recently, as wide-bandgap semiconductor materials have been intensively studied for high-power RF and switching electron devices, we reconstructed SIPM for these by using visible lasers. We demonstrated two-dimensional (2-D) characterization of interfacial reaction and surface damages in SiC, GaN, and Oxide-semiconductor Schottky contacts (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). We also demonstrated that SIPM is available for semiconductor/semiconductor (S/S) hetero-interfaces and metal-insulator-semiconductor (MIS) interfaces (19,20).…”
Section: Introductionmentioning
confidence: 98%